Eat pray love. One Woman's Search for Everything - Gilbert E. Elizabeth (London, Bloomsbury, 2010)
This beautifully written, heartfelt memoir touched a nerve among both readers and reviewers. Elizabeth Gilbert tells how she made the difficult choice to leave behind all the trappings of modern American success (marriage, house in the country, career) and find, instead, what she truly wanted from life. Setting out for a year to study three different aspects of her nature amid three different cultures, Gilbert explored the art of pleasure in Italy and the art of devotion in India, and then a balance between the two on the Indonesian island of Bali. By turns rapturous and rueful, this wise and funny author (whom Booklist calls "Anne Lamott's hip, yoga- practicing, footloose younger sister") is poised to garner yet more adoring fans.